2020
DOI: 10.1097/md.0000000000019613
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is associated with lower health care costs among Taiwanese individuals with diabetes mellitus

Abstract: The economic burden of diabetes has increased over time with disease severity. Previous publications investigating the effects of physical activity (PA) on medical costs have made use of small sample sizes. We assessed the relationship between PA and 1-year medical expenditure among Taiwanese patients with type-2 diabetes mellitus (T2DM). Data were recruited from three governmental databases, including the 2012 adult preventive health service database. Participants were grouped as inactive (no exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Most patients with NAFLD exhibit the so-called triple-hit behavioral phenotype consisting in (i) sedentary behavior, (ii) low physical activity, and (iii) poor diet [ 118 ]. Short-term benefits of physical activity in NAFLD are well demonstrated [ 119 ] and it is likely that physically active individuals with NAFLD, similar to patients with T2D, may be protected from developing complications of their disease leading to a reduced healthcare financial burden [ 120 ]. On these grounds, it seems relevant that patients with NAFLD should always be classified along a semi-quantitative scale of sedentary behavior defined as time spent sitting or lying with low energy expenditure (e.g., assessed with TV watching time) and physical activity (along a scale of intensity and time spent on exercising per week).…”
Section: Diagnosismentioning
confidence: 99%
“…Most patients with NAFLD exhibit the so-called triple-hit behavioral phenotype consisting in (i) sedentary behavior, (ii) low physical activity, and (iii) poor diet [ 118 ]. Short-term benefits of physical activity in NAFLD are well demonstrated [ 119 ] and it is likely that physically active individuals with NAFLD, similar to patients with T2D, may be protected from developing complications of their disease leading to a reduced healthcare financial burden [ 120 ]. On these grounds, it seems relevant that patients with NAFLD should always be classified along a semi-quantitative scale of sedentary behavior defined as time spent sitting or lying with low energy expenditure (e.g., assessed with TV watching time) and physical activity (along a scale of intensity and time spent on exercising per week).…”
Section: Diagnosismentioning
confidence: 99%
“…studies associated physical inactivity to costs due to cardiovascular disease or diabetes [25][26][27] and few estimated costs due to breast cancer [7,9]. The few studies that associated costs to breast cancer were focused on leisure-time physical inactivity [7] and not with physical inactivity in all domains (leisure, transport, domestic activities, work), as was the case in the present study.…”
Section: Plos Onementioning
confidence: 71%
“…The economic burden of physical inactivity was studied by authors from different countries who found high costs for health systems due to physical inactivity [25][26][27]. Most of these…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of local governments in providing age-friendly neighbourhoods is acknowledged [ 105 , 113 ]. Our findings have implications for policy makers and service providers aiming to build and maintain age-friendly communities that support older individuals’ PA, in turn benefitting health and potentially reducing care costs [ 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%